Enhancement of water saving capacity in rice (Oryza sativa) through plant growth-promoting rhizobacteria (PGPR) stimulation - Alias, Azie Asmiati (2015)
Research related to technologies in water saving capacities can lead to an increase in the water use efficiency in crop production. New water saving technologies potentially act as substitutes for conventional cultivation technique which has a high demand for water consumption (3000 L water/ kg grain yield) in rice cultivation. Rice is highly sensitive to water deficiency and may cause a decline in vegetative growth and crop yield. Hence, a strategic and economic water management system known as soil saturated cultivation (SSC) was applied in this experiment in the presence of plant growth-promoting rhizobacteria (PGPR). During growth development, water was maintained under saturated and flooded conditions as in conventional system. This experiment was conducted in a growth chamber for 28 days at Soil Microbiology Lab, Department of Land Management, Universiti Putra Malaysia. The objective of this experiment was to measure the effectiveness of water saving capacity on vegetative growth of rice and to measure the ability of PGPR in enhancing the stimulation of water saving capacity in rice plant. The hypotheses were: (1) PGPR inoculum has the ability to fix nitrogen (N2), solubilize phosphate and potassium and produce Indole-3-acetic acid (IAA), (2) PGPR used is able to stimulate vegetative growth of rice in saturated soil condition, (3) PGPR used can potentially save the usage of NPK fertilizer, (4) PGPR helps the rice plant to endure and tolerate water stress. This experiment consisted of 8 treatments under different conditions (saturated and flooded): Inoculated and non-inoculated with PGPR (UPMB-10) at a fertilizer rate of 33% N, 33% P and 33%K; Inoculated and non-inoculated with PGPR (UPMB-10) at 100% NPK fertilizer rate. Based on this experiment the vegetative growth of paddy in a saturated condition with application of UPMB-10 showed good growth, equivalent to flooded conditon treatment with and without UPMB-10. Result from each treatment with UPMB-10 inoculation under saturated condition showed significant results through observations of the following parameters: plant height, dry weight and fresh weight, root volume and area and, total nitrogen content in plant tissue. UPMB-10 have the ability and potentitally to enhance the water rice saving capacity by saving 12 % water compared to the conventional water consumption. Besides, it has an added beneficial effect in reducing 33% of the NPK fertilizer input for rice production under flooded system (conventional)